2023
DOI: 10.1098/rstb.2022.0019
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific trait variation and changing life-history strategies explain host community disease risk along a temperature gradient

Abstract: Predicting how climate change will affect disease risk is complicated by the fact that changing environmental conditions can affect disease through direct and indirect effects. Species with fast-paced life-history strategies often amplify disease, and changing climate can modify life-history composition of communities thereby altering disease risk. However, individuals within a species can also respond to changing conditions with intraspecific trait variation. To test the effect of temperature, as well as inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Selective removal of non-hosts, or low-competence hosts, should increase the prevalence of disease on the remaining high competence hosts, whereas removal of highly competent hosts is likely to reduce disease (Borer et al, 2009;Johnson et al, 2013). A key predictor of pathogen infection in many contexts is host pace of life, with fast growing plant and animal hosts suffering more infection (Cappelli et al, 2020;Cronin et al, 2010;Halliday et al, 2023;Johnson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective removal of non-hosts, or low-competence hosts, should increase the prevalence of disease on the remaining high competence hosts, whereas removal of highly competent hosts is likely to reduce disease (Borer et al, 2009;Johnson et al, 2013). A key predictor of pathogen infection in many contexts is host pace of life, with fast growing plant and animal hosts suffering more infection (Cappelli et al, 2020;Cronin et al, 2010;Halliday et al, 2023;Johnson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Selective removal of non‐hosts, or low‐competence hosts, should increase the prevalence of disease on the remaining high competence hosts, whereas removal of highly competent hosts is likely to reduce disease (Borer et al., 2009; Johnson et al., 2013). A key predictor of pathogen infection in many contexts is host pace of life, with fast growing plant and animal hosts suffering more infection (Cappelli et al., 2020; Cronin et al., 2010; Halliday et al., 2023; Johnson et al., 2012). According to the leaf economics spectrum, “fast‐growing” plants with rapid growth, short leaf life spans and high specific leaf area (SLA), invest relatively little in defences, while “slow‐growing” species, with longer leaf life spans, slower growth rate and low SLA, invest more resources into defences (Reich, 2014; Wright et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Disease spread can also depend on how temperature interacts with traits in host communities [20,21]. In a thorough field study set in the Swiss Alps, Halliday et al [22] found-complex relationships between trait variation in plant communities driven by temperature gradients and prevalence of infection in those communities. Together, these three studies highlight that to predict disease dynamics under climate change, we should consider multiple traits at the interface of host-pathogen interactions and their variation within species and communities.…”
Section: Introductionmentioning
confidence: 99%